PENGARUH KERAGAMAN PRODUK DAN PEMASARAN ONLINE TERHADAP MINAT BELI KONSUMEN DI SHOPEE - Ginting, Anjeli Sibina Br; Susanthi, Putu Rani (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2024)
This study aims to determine the effect of product diversity and online marketing on buying interest in fashion products in e-commerce shopee. In this study, a quantitative method was used in which data were obtained from survey results and questionnaire data processing based on statistical procedures. Based on Lemeshow’s formula, the sample in this study was 97 respondents. In this study, it has been found that the product diversity variable has an influence on buying interest with a significance level value of 0.003 smaller than 0.050, the online marketing variable (X2) has an influence on consumer buying interest (Y) with a significant value of 0.000 smaller than 0.050, and based on the results of the F test shows that Fcount 55.808> Ftable 3.09 with a sig value of 0.000 <0.050. While the results of the analysis of the coefficient of determination with the value of R Square (R2) is 0.543. So it can be concluded that the variable Product Diversity (X1) and Online Marketing Strategy (X2), simultaneously have a significant effect on the Purchase Interest variable (Y) by 54.3%, while the remaining 45.7% is influenced by other variables outside this study, which means that the third hypothesis (H3) is accepted, so it can be concluded that product diversity, and online marketing strategies simultaneously affect buying interest.